Sobre o saber que não se sabe necessário à formação e práxis do educador: palavras, silêncio, ditos e (contra)ditos. - Braga, José Olinda (2008)
There are various searches for descriptive understanding of what occurs between teachers and students in their meetings and disagreements in the classroom. In addition to a look that is restricted to an attempt to describe the different contexts, the construction of new and unusual educational activities, something calls us from that place, insisting and resisting, a place where everything flows, or where everything stiffen. More ontological although the analysis of contexts and pretexts of the facilitate or difficult act of teaching, which will promote new opportunities for construction of technology, knowledge and the development of more favorable learning, is located in such places and instances, the intermingling of desires hacking, shortcuts in the direction of roads and footpaths that take the place of execution of educational practice. This research aims to elucidate what is behind any announces possible objectification act of education: place the same desire realized, the order of not known, that by default or the trailer of the joints conscious and volitional, leads the process of becoming one teacher being. This is the way to describe, locate the advent of the teacher who moved by existential contexts, forged by imperatives, it is front of the student, with his knowledge needed to practice with their teacher or divestitures; skills and inappetence; political positions, engagement, everything what in your environment that ensures it in the web of meanings that is as subjects in the hard work of reproduction of meaning to the world. Judging the opportunity to view the tangle that is based on the affection and disaffection, the size of knowing that it is not known, but it is necessary to practice the educator, and both insist on saying that during the speech teachers, the clipping of search focuses the narrative of teachers, where they highlighted the stories of life and training, memories of significant meetings with students from that breaks out the possibility of seizing the subtleties of neglected pieces of debris that often do not account in stories of education, of love and disappointment experienced and preserved in memory of those who dare to transgress impossible to educate